Epigenetic modifications and diabetic nephropathy - Marpadga A. Reddy; Jung Tak Park; Rama Natarajan (The Korean Society of Nephrology, 2012)
Diabetic nephropathy (DN) is a major complication associated with both type 1 and type 2 diabetes, and a leading cause of end-stage renal disease. Conventional therapeutic strategies are not fully efficacious in the treatment of DN, suggesting an incomplete understanding of the gene regulation mechanisms involved in its pathogenesis. Furthermore, evidence from clinical trials has demonstrated a "metabolic memory" of prior exposure to hyperglycemia that continues to persist despite subsequent glycemic control. This remains a major challenge in the treatment of DN and other vascular complications. Epigenetic mechanisms such as DNA methylation, nucleosomal histone modifications, and noncoding RNAs control gene expression through regulation of chromatin structure and function and post-transcriptional mechanisms without altering the underlying DNA sequence. Emerging evidence indicates that multiple factors involved in the etiology of diabetes can alter epigenetic mechanisms and regulate the susceptibility to diabetes complications. Recent studies have demonstrated the involvement of histone lysine methylation in the regulation of key fibrotic and inflammatory genes related to diabetes complications including DN. Interestingly, histone lysine methylation persisted in vascular cells even after withdrawal from the diabetic milieu, demonstrating a potential role of epigenetic modifications in metabolic memory. Rapid advances in high-throughput technologies in the fields of genomics and epigenomics can lead to the identification of genome-wide alterations in key epigenetic modifications in vascular and renal cells in diabetes. Altogether, these findings can lead to the identification of potential predictive biomarkers and development of novel epigenetic therapies for diabetes and its associated complications.